Penyusunan Sistem Informasi dan Pencatatan Akuntansi pada CV. CAKRAWALA - Kennardi Tanujaya; Isnaini Ria Angraini (Universitas Internasional Batam, 2021)
Cakrawala is a business that is engaged in catering services. The catering business owner still uses a manual accounting recording system for each transaction. Therefore, community service activities are carried out to design an accounting recording system. A system designed to facilitate every transaction that occurs in each accounting period at CV. Cakrawala. Creation of a system designed and implemented during the months of September - December which will be used accordingly. With the creation of this system, it is hoped that the CV. Cakrawala can be consistent in the use of a financial reporting recording system in order to produce financial reports that can be used as a basis for decision making.